2011
DOI: 10.3892/ol.2011.271
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic implications of genetic alterations in oral cancers

Abstract: This study evaluated the clinicopathological and prognostic implications of genetic alterations characterizing oral squamous cell carcinoma(OSCC). Comparative genomic hybridization(CGH) was used to identify chromosomal alterations present in primary OSCCs obtained from 97 pateints. In this population, tobacco use was a significant risk factor for OSCC. By contrast, all 97 of our samples are negative for human papillomavirus (HPV) DNA integration, which is another known risk factor for OSCC in certain populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
(43 reference statements)
3
20
1
3
Order By: Relevance
“…Some studies described a reduced overall survival of HNSCC patients associated with high-level PPFIA1 amplification (Akervall et al, 1995;Ashman et al, 2003;Bockmuhl et al, 2000;Pathare et al, 2011;Wreesmann et al, 2004). We did not observe such correlation in the present study.…”
Section: Discussioncontrasting
confidence: 82%
“…Some studies described a reduced overall survival of HNSCC patients associated with high-level PPFIA1 amplification (Akervall et al, 1995;Ashman et al, 2003;Bockmuhl et al, 2000;Pathare et al, 2011;Wreesmann et al, 2004). We did not observe such correlation in the present study.…”
Section: Discussioncontrasting
confidence: 82%
“…According to GLOBOCAN 2008, the incidence of OSCC in India is 69,820 cases annually. However, despite many advances in its treatment, there are still many lacunae in the existing treatment strategies as a result of which the 5-year survival rate of OSCC has remained unchanged during the last few decades (26). It is thus imperative to identify novel therapeutic targets for OSCC.…”
mentioning
confidence: 99%
“…The reported HPV prevalence in oral cancers in India varied from 0 to 100% in studies using biopsies in cases and PCR assay for HPV detection and genotyping. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For the studies using a methodology similar to ours (oral brushing to collect epithelial cells instead of biopsy, combined with PCR for detection and genotyping), the prevalence reported for oral cancer cases was 31.5 26 and 32.4%. 15 Our results are in agreement with two studies conducted in Gujarat and Mumbai in West India, which reported a null prevalence of HPV in oral cancer using biopsies (in one of the studies, only HPV-16 and 18 were tested).…”
Section: Discussionmentioning
confidence: 99%
“…15 Our results are in agreement with two studies conducted in Gujarat and Mumbai in West India, which reported a null prevalence of HPV in oral cancer using biopsies (in one of the studies, only HPV-16 and 18 were tested). 27,28 However, considering the fact that only two previous studies showed a null prevalence in oral cancer in India, we explored other explanations for these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation